Characterization of a small Mediterranean island end-users' electricity consumption: The case of Lampedusa. (November 2017) - Beccali, M.; Bonomolo, M.; Di Pietra, B.; Ippolito, M.G.; La Cascia, D.; Leone, G.; Lo Brano, V.; Monteleone, F.; Zizzo, G.
Highlights: Real electricity consumption data for Mediterranean small islands residential end-users are presented. Typical domestic and hotel-type end-users in small islands are identified and characterized. Electric storage water heaters considerably influence the daily load profile of domestic end-users. Aggregated daily load profiles are built using a bottom up approach based on on-field electricity measurements. Abstract: The paper presents the results of a study carried out on Lampedusa Island (Italy) and based on the survey of electricity consumption data. The main outcomes of the study are: the characterization of the energy demand of private houses and hotels in Italian small islands with significant touristic flows during the summer period; the identification of inefficient use of the electric loads; the construction of aggregated load profiles for clusters of homogeneous domestic end-user to be used for implementing Demand Response strategies. The study shows how electricity consumption in Mediterranean small islands are very high with respect to the national average and lays the basis for future studies on the impact of automation and Renewable Energy Sources on the energy supply-demand sustainability of the island.